The Critical Thinking Skill Gap in the Kenyan Education Curriculum: The 21st Century Skills for the Global Citizen - Ongesa, Cosmas Masega (Journal of Interdisciplinary Studies in Education, 2020)
Across the globe, the learning goals of elementary, secondary, and higher education curricula emphasize the development of the critical thinking approach. In Kenya, the curriculum mentions developing critical thinking as one of its objectives, but a critical review reveals that the education system prioritizes competitive exams and rote memorization over critical thinking and other vital 21st-century skills. In this paper, I argue that educational authorities can achieve this objective if they critically evaluate the purpose of education regularly to ensure that there is an alignment between the stated goals and practice. They also need to make sure that the education they provide leaves no learner behind.